KERJASAMA PERTAHANAN AMERIKA SERIKAT DAN FILIPINA DALAM KONTEKS BUCKPASSING TAHUN 2014-2016 - Asano, Diba Amalia; Saeri, M. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The purpose of this research is to explain about the strategy that United States of America use to offset the rise of the China in Asia Pacific. The strategy was buckpassing and the form of that strategy is the cooperation between the United States of America and the Philippines in Enhanced Defense Cooperation Agreement (EDCA) since 2014.This research is using realism perspective, in this perspective state is the main actor and national security is the main concern. Struggle for power is also become main concern of the realists, it was showed by the country that always take into account about cost and benefit of every action that they did. This research is also using national interest theory which is explain why power is important to be obtain and maintained.The rise of China as a new power brings up a variety of speculation and also threats around its area. It happened because they not only improve the ability of their country but also began to disturb Asia Pasific region with their claim about South China Sea claims. The United States the use various way to maintain its influence and power in Asia Pacific region by improving the relationship that the United States has with its allies in there. Change in foreign focus also made considering the Asia Pacific region especially the South China Sea has significance for the United State.Keyword: Enhanced Defense Cooperation Agreement, Buckpassing, Strategy, China